Predictors of Sexual Satisfaction After Cancer in Women - Ni Putu Wulan Purnama Sari; Maria Manungkalit (Malahayati Nursing Journal, 2023)
ABSTRACT Gynecological cancers are frequently found in women. There are various sexual-related symptoms influencing the fulfillment of sexual needs among women living with cancer. In addition, psychological burden due to cancer may induce negative emotional stimulus potentially decreases sexual satisfaction. This study aimed at analyzing the predictors of sexual satisfaction after cancer in women. This cross-sectional study involved 35 women living with cancer in two congested communities in Surabaya, Indonesia. The sexual satisfaction questionnaire was used to collect the data of sexual satisfaction. Dest alcriptive statistic and regression test were used in data analysis. The majority were short term survivors of breast cancer under chemotherapy. Surprisingly, 100% respondents reported none sexual-related complaint and sex-generated negative emotions could not predict sexual satisfaction significantly (p=0.087). Sexual satisfaction was mostly sufficient (Mean ± SD = 30.34 ± 5.78) with afraid of sexual partner dissatisfaction being the strongest predictor of sexual satisfaction (p=0.000). It was accounted for 50.9% variances of sexual satisfaction in this population (R2=0.509). Sexual satisfaction is sufficient in women living with cancer who had none sexual-related complaint. It is predicted strongly by afraid feeling of sexual partner dissatisfaction. Sex-generated negative emotions cannot predict it significantly.  Keywords: Cancerous Women, Female Cancer, Sexual Life, Sexual Needs, Sexual Satisfaction.